2015
DOI: 10.1149/06447.0015ecst
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Study for Application in Green Housing

Abstract: We report on antibacterial and antifungal properties study of silver nanoparticles in applications relating to straw bale construction. Humidity related growth of microorganisms in green constructions is of concern as it can induce health problems among the house residents and also can cause lower durability of ecologically friendly construction materials. We provide a comparative analysis of the effects of silver nanoparticles on most common house-colonizing fungi and bacteria. Outdoor tests demonstrated an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The HRSTEM study showed that Ag NPs are spherical with a size distribution ranging from 2 to 10 nm, but several bigger Ag NPs of 50 nm were also observed, suggesting that the value obtained by Scherrer calculation is not misleading. Thermogravimetric analysis did not show any weight loss, confirming the absence of organic species on the surface of the Ag MNPs [9]. The antifungal properties of silver nanoparticles.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The HRSTEM study showed that Ag NPs are spherical with a size distribution ranging from 2 to 10 nm, but several bigger Ag NPs of 50 nm were also observed, suggesting that the value obtained by Scherrer calculation is not misleading. Thermogravimetric analysis did not show any weight loss, confirming the absence of organic species on the surface of the Ag MNPs [9]. The antifungal properties of silver nanoparticles.…”
Section: Discussionmentioning
confidence: 68%
“…Synthesis and method. Ag MNPs were prepared by non-hydrolytic sol-gel method [22,23] using Ag acetate precursor (99%, Aldrich) and have been described in a recent paper published elsewhere [9]. The prepared Ag MNPs in ethanol solutions (10 mg/L and 40 mg/L) were poured into two vessels, which contained straw bales samples (10 g).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a previous study, the antimicrobial effect of AgNPs on fungal pathogens was measured by the implementation of a typical agar well diffusion technique [70]. Consequently, the antimicrobial activity of the synthesized AgNPs utilizing different parts of the common bean (root, stem and leaf) has been thoroughly investigated.…”
Section: Determination Of Antimicrobial Activity By Agar Well Diffusion Methodsmentioning
confidence: 99%